2015
DOI: 10.1089/ars.2013.5706
|View full text |Cite
|
Sign up to set email alerts
|

Redox-Sensitive Structure and Function of the First Extracellular Loop of the Cell–Cell Contact Protein Claudin-1: Lessons from Molecular Structure to Animals

Abstract: The paracellular cleft within epithelia/endothelia is sealed by tight junction (TJ) proteins. Their extracellular loops (ECLs) are assumed to control paracellular permeability and are targets of pathogenes. We demonstrated that claudin-1 is crucial for paracellular tightening. Its ECL1 is essential for the sealing and contains two cysteines conserved throughout all claudins. Aims: We prove the hypothesis that this cysteine motif forms a redox-sensitive intramolecular disulfide bridge and, hence, the claudin-1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 66 publications
1
38
0
Order By: Relevance
“…The unique properties of Tric are supported by the short peptide double chain of Tric-ECL2, including two specific prolines, but lacking b-sheet and a-helix elements. Consequently, the Tric-ECL2 structure is neither compatible with the Occl-ECL2 (2) nor with the ECL1 of Clds, both of which share the latter structural features (8). This further explains why heterophilic associations are impossible for Tric in the 3-cell contact.…”
Section: Fig 5 Transfection Of Cysteine Mutants Of Yfp-tricellulin mentioning
confidence: 94%
See 1 more Smart Citation
“…The unique properties of Tric are supported by the short peptide double chain of Tric-ECL2, including two specific prolines, but lacking b-sheet and a-helix elements. Consequently, the Tric-ECL2 structure is neither compatible with the Occl-ECL2 (2) nor with the ECL1 of Clds, both of which share the latter structural features (8). This further explains why heterophilic associations are impossible for Tric in the 3-cell contact.…”
Section: Fig 5 Transfection Of Cysteine Mutants Of Yfp-tricellulin mentioning
confidence: 94%
“…MDCK-II, Madin-Darby canine kidney cell line; TJ, tight junction; Tric, tricellulin; TM, transmembrane domain. 8 CORDING ET AL.…”
Section: Fig 5 Transfection Of Cysteine Mutants Of Yfp-tricellulin mentioning
confidence: 99%
“…C5C2/shifted is truncated (4 aa, C‐terminal) and prolonged (5 aa, N‐terminal). C2C2 was derived from the ECL1 of murine claudin‐2 (aa 53–81) and used as a control . Native Cys were replaced by Ser.…”
Section: Methodsmentioning
confidence: 99%
“…The claudin‐1 peptidomimetic C1C2 dose‐dependently and reversibly opens the perineurial barrier of peripheral nerves in rats, allowing small drugs that typically do not permeate the perineurium to do so in a defined time frame . Analysis of the mode of action revealed that C1C2 causes redistribution of claudins from junctions to the cytosol, disturbs TJ‐strand morphology, and reduces claudin‐1 expression …”
Section: Introductionmentioning
confidence: 99%
“…The two conserved cysteines in the signature motif of the claudins have been found to form an intramolecular disulfide bond and mediate paracellular tightening. 11 In EMP-1 the intramolecular disulfide bond cannot be formed, as only one of these cysteines is conserved (Fig. 1, left).…”
mentioning
confidence: 99%